Assessing cardiovascular risk in ATM heterozygotes - Kotchetkoff,Elaine Cristina de Almeida (2018)
Summary Objective: To evaluate the carotid intima-media complex (CIMC) thickness and lipid metabolism biomarkers associated with cardiovascular risk (CR) in parents of patients with ataxia-telangiectasia and verify an association with gender. Method: A cross-sectional and controlled study with 29 ATM heterozygotes and 14 healthy controls. Biochemical tests and CIMC thickness measurement were performed. Results: The mean CIMC measurement in heterozygous ATM was 0.72 ± 0.1 mm (minimum: 0.5 mm and maximum: 1.0 mm). Noticed high percentage of amounts above 75 percentile compared to the population referential (16 [76.2%]), without any significant statistical differences between the female and the male gender (11/15 [73.3%] vs. 5/6 [83.3%]; p=0.550). The comparison between heterozygous and controls, stratified by gender, showed that in heterozygous ATMs, women had higher concentrations of HDL-c compared to men, as well as higher values of hs-CRP in relation to the control women. In heterozygous ATMs, stratified by gender, the correlation between HDL-c and hs-CRP was inversely proportional and stronger among women, with a tendency to statistical significance. Conclusion: Heterozygous ATMs did not differ from controls in relation to the biomarkers studied related to CR. However, most of them presented increased CIMC, independent predictor of death, risk for myocardial infarction and stroke, compared to the referential for the same age group. This finding suggests CR in the heterozygous ATM and shows to the need to monitor CIMC thickness and nutritional orientations.